The mediating role of organizational culture between transformational leadership and organizational performance in SMEs - Peña, Jorge (2024)
Purpose: Considering the entrepreneurship nature and the high number of small and medium enterprises (SMEs) in the Latin American region, this study seeks to empirically test the relationship between organizational culture (OC), transformational leadership (TF) and organizational performance (OP) to support their long-term survival. Design/methodology/approach: Under a post-positivism paradigm, quantitative approach and correlational scope, this research analyzed the interrelationship between OC, TF and OP across Peruvian SMEs. Confirmatory factor analysis (CFA) and structural equation modeling (SEM) were used to test the hypotheses based on the responses of 276 SMEs’ top executives from the commerce, services, manufacturing, construction and agriculture industries. Findings: OC fully mediates the relationship between TL and OP. Although TF solely does not drive OP, the mediating effect of OC is crucial for SMEs’ long-term survival, especially considering their contribution to employment, poverty reduction and GDP in developing countries. Entrepreneurial transformational leaders inspire their followers to achieve goals, strive to develop individual skills, transmit confidence and leave aside their own interests to focus on the common goal of growing their entrepreneurship competitively. Originality/value: The three variables under analysis have been applied to large companies and SMEs. However, this research enriches previous findings, highlighting the necessity for an adequate OC derived from an entrepreneur with TL, contributing to the survival of SMEs, whose results are critical for developing countries’ economies.